Looking for nebular He ii emission south of the multiple-massive star system, HD 5980 - Sixtos, José Andrés; Wofford, A; Sander, Andreas A. C.; Peimbert, A (Monthly notices of the Royal Astronomical Society, 2023)
The nebular He ii λ1640 emission line is observed in star-forming galaxies out to large distances and can be used to constrain the properties of sources of He+-ionizing photons. For this purpose, it is crucial to understand which are the main stellar sources of these photons. In some nearby metal-poor starburst galaxies, nebular He ii λ4686 (optical equivalent) is accompanied by a broad underlying component, which is generally attributed to formation in the winds of classical (He-burning) Wolf-Rayet stars, primarily of the WN subtype. In such cases, the origin of the nebular component has been proposed to be the escape of He+-ionizing photons from the winds of the WN stars, at least partially. We use archival long-slit observations obtained with Focal Reducer Low Dispersion Spectrograph (FORS1) on the Very Large Telescope to look for nebular He ii λ4686 emission south of the WN6h + WN6-7 close binary in HD 5980. We only find broad He ii λ4686 emission, as far as ∼7.6 pc from the binary. A comparison with observations obtained with Space Telescope Imaging Spectrograph (STIS) on the Hubble Space Telescope, at a similar orbital phase, shows that the FORS1 broad He ii emission is likely contamination from the multiple-star system HD 5980. We use models to show that no significant He+-ionizing flux is expected from the WN stars in HD 5980 and that when similar stars are present in a coeval stellar population, the O stars can be far greater emitters of He+-ionizing radiation.